2016
DOI: 10.1016/j.jaap.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for producing biochars with minimum PAH contamination

Abstract: With the aim to develop initial recommendations for production of biochars with minimal contamination with polycyclic aromatic hydrocarbons (PAHs), we analysed a systematic set of 46 biochars produced under highly controlled pyrolysis conditions. The effects of the highest treatment temperature (HTT), residence time, carrier gas flow and typical feedstocks (wheat / oilseed rape straw pellets (WSP), softwood pellets (SWP)) on 16 US EPA PAH concentration in biochar were investigated. Overall, the PAH concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
105
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 42 publications
5
105
0
Order By: Relevance
“…Also, it was found that the conversion technology is a factor to be considered. Regarding the temperature, Buss et al (2016), after analyzing the samples, were unable to recommend a particular pyrolysis temperature for the production of biochar with low PAH content. González et al (2017).…”
Section: Effect Of Pyrolysis Process Conditions On Pahs Concentrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, it was found that the conversion technology is a factor to be considered. Regarding the temperature, Buss et al (2016), after analyzing the samples, were unable to recommend a particular pyrolysis temperature for the production of biochar with low PAH content. González et al (2017).…”
Section: Effect Of Pyrolysis Process Conditions On Pahs Concentrationmentioning
confidence: 99%
“…Moreover, Devi and Saroha (2015) and Alburquerque et al (2015) reported a decreasing PAHs concentration when the temperature increased, similar to our results. Buss et al (2016) collected and analyzed 46 biochar produced under different operational conditions and different configuration of reactors and concluded that feedstock characteristics highly influenced on PAH concentrations. Also, it was found that the conversion technology is a factor to be considered.…”
Section: Effect Of Pyrolysis Process Conditions On Pahs Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, biochar adsorbs hydrophobic organic pollutants in the soil [12,13]. However, the process of biochar production (torrefaction) is accompanied by the formation of polycyclic aromatic hydrocarbons (PAHs) as a result of Diel-Alder reaction occurring during the process [14]. These hydrocarbons are considered to be toxic, and for this reason, their emissions to the environment are legally limited and strictly monitored.…”
Section: Introductionmentioning
confidence: 99%